Neue zoophage Gallmücken-Gattungen (Diptera: Itonididae). - Möhn, Edwin (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural Actsvasta Möhn, 1955 (Chiliodiplosis), spec. n.Chiliodiplosis Möhn, 1955 (Itonididae), gen. n.Phonodiplosis Möhn, 1955 (Itonididae), gen. n.casta Möhn, 1955 (Phonodiplosis), spec. n.